2021
DOI: 10.3390/microorganisms9061288
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Improve Eating Disorders in Mandarin Fish (Siniperca chuatsi) Induced by a Pellet Feed Diet via Stimulating Immunity and Regulating Gut Microbiota

Abstract: Eating disorders are directly or indirectly influenced by gut microbiota and innate immunity. Probiotics have been shown to regulate gut microbiota and stimulate immunity in a variety of species. In this study, three kinds of probiotics, namely, Lactobacillus plantarum, Lactobacillus rhamnosus and Clostridium butyricum, were selected for the experiment. The results showed that the addition of three probiotics at a concentration of 108 colony forming unit/mL to the culture water significantly increased the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 148 publications
1
10
0
Order By: Relevance
“…According to our results, in addition to the increased SOD, CAT, GPx, GST, GR, and G6PD activity in the groups containing 1.0 × 10 7 CFU/ml A, C, and D bacteria, MDA was also at a very low level compared to the control and B groups in liver. These results are consistent with those obtained by Kong et al (2021) and Chen et al (2021).…”
Section: Tissues Treatmentsupporting
confidence: 93%
See 2 more Smart Citations
“…According to our results, in addition to the increased SOD, CAT, GPx, GST, GR, and G6PD activity in the groups containing 1.0 × 10 7 CFU/ml A, C, and D bacteria, MDA was also at a very low level compared to the control and B groups in liver. These results are consistent with those obtained by Kong et al (2021) and Chen et al (2021).…”
Section: Tissues Treatmentsupporting
confidence: 93%
“…Exposure to different substances causes damage to the gills, difficulty in breathing, decreased oxygen uptake, and a decrease in critical swimming speed as a behavioral effect. The host gut microbiota affects the central nervous system by affecting local oxidative stress levels and the permeability of the gut, then subsequently the behavioral characteristics of the host (Chen et al 2021). In this research, we observed that acute applications of bacterial strains significantly reduce the critical swimming speed, especially in group B. AChE inhibition is believed to be effective in this poor performance (Domingues et al 2016).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The gut microbiota can affect host health and is associated with multiple diseases, such as diabetes and depression [ 8 , 9 ]. The colonization or increase of probiotics is beneficial to the treatment of diseases [ 10 ]. However, the increase in some microbes in the intestine can promote the occurrence of diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since aquatic animals are continuously exposed to water, the structure and composition of their mucosal microbiota are strongly affected by the habitats [42]. Previous studies had demonstrated that the intestinal microbial composition of fishes, shrimps, and crabs were affected by the surrounding environment (e.g., water or sediments) [43][44][45] or feeding strategy [46,47]. However, most of these studies were carried out by changing the feed composition and geographical location, or through environmental stress.…”
Section: Introductionmentioning
confidence: 99%